Effects of intravenous propofol combined with opioids on euphoria in patients undergoing painless gastrointestinal endoscopy: protocol for a randomized double-blind placebo-controlled trial - Yu, Youjia; Ma, Qingfang; Du, Fengxia; Zhang, Xiang; Shao, Chunyan; Li, Yan; Ma, Chuntao (Frontiers in Pharmacology, 2025)
BackgroundIn recent years, the rapid increase in gastrointestinal endoscopic procedures has posed new demands and challenges for painless and comfortable medical care. Intravenous anesthetics may increase postoperative euphoria in patients. This study aims to evaluate the effects of intravenous propofol combined with fentanyl, nalbuphine, or saline on euphoria in patients undergoing painless gastrointestinal endoscopy.MethodsThis is a single-center, randomized, double-blind, placebo-controlled trial protocol involving 285 adult patients scheduled for bidirectional endoscopy. Participants will be randomly assigned to either the fentanyl group, the nalbuphine group, or the placebo group (n = 95 per group). The fentanyl group will receive propofol + fentanyl; the nalbuphine group will receive propofol + nalbuphine; and the placebo group will receive propofol + saline. The primary outcome is the Addiction Research Center Inventory (ARCI) - Morphine–Benzedrine Group (MBG) scores at 30 min post-awakening. Secondary outcomes will include ARCI-MBG scores at 1 week and 1 month postoperatively; ARCI total scores at 30 min post-awakening, 1 week, and 1 month postoperatively; ARCI-Pentobarbital, Chlorpromazine, Alcohol Group (PCAG) scores at 30 min post-awakening, 1 week, and 1 month postoperatively; ARCI-Lysergic Acid Diethylamide (LSD) scores at 30 min post-awakening, 1 week, and 1 month postoperatively; Pittsburgh Sleep Quality Index scores at 1 week and 1 month postoperatively; and dream descriptions (none, pleasant, or nightmare) at 30 min post-awakening; The Surgical Pleth Index assessed at the time of endoscope insertion. Safety outcomes will include desaturation, hypotension, nausea or vomiting, dizziness, headache, choking cough, involuntary movement, bradycardia, and airway intervention. Data will be analyzed following a modified intention-to-treat approach.DiscussionThis study aims to provide high-quality evidence for the potential addictive properties and safety of propofol combined with opioids in gastrointestinal endoscopy procedures.Ethics and DisseminationThis study was approved by the Ethics Committee of Xiangcheng People’s Hospital of Suzhou (2024-KY-05) on 19 August 2024, and is registered with the Chinese Clinical Trial Registry (ChiCTR2500096595). All participants will provide written informed consent, and the study will adhere to the principles of the Declaration of Helsinki. The findings will be published in a peer-reviewed journal. URL: https://www.chictr.org.cn/showproj.html?proj=252367.